Psychosocial factors related to adolescent depressive symptom: systematic literature review - Ktut Dianovinina; Endang Retno Surjaningrum (Intelektual Pustaka Media Utama, 2023)
Depressive disorder is currently ranked fourth in the world in the prevalence of mental disorders affecting adolescents. This position encourages the author to explore depression risk and protective factors of the particular population. This study aimed to present factors of risk or protection to the symptom development of adolescent depression. We conducted a systematic review of the literature searching in Science Direct and Springerlink to inquire about relevant articles. There were 21 studies published from 2016 to 2020 included in this study. As a result, 37 factors were categorized as psychological (personality trait, cognitive, emotion, behavior, and coping strategy) and social factors (social support, factors related to parents, and negative life events). Some factors are positively correlated with depression, while others negatively correlate with depression. The study results aspire to be the intervention target for minimizing the emergence symptoms of adolescent depression by developing positive personality traits, positive thinking, practical coping strategies skills to find social support and development of positive parenting practice.